Advertising A New Approach (RLE Advertising) - Taplin, Walter (Routledge, 2013)
Walter Taplin here presents the first fruits of his exhaustive enquiry into the causes of this massive feature of contemporary life. Advertising has deeper and more interesting sources than the mere desire of manufacturers to secure markets, or of high-pressure salesmen to secure commissions. Taplin explores the nature of human wants, examines the functions and limitations of information, and distinguishes the good from the bad in the arts of persuasion. His approach to the subject is indeed a new one, and of the greatest value to all who wish to understand one of the most powerful forces of the day. First published in 1960.